Selected topics in the history of biochemistry, personal recollections. - Semenza, G., 1928-; Jaenicke, R. (Rainer), 1930- (Comprehensive biochemistry. History of biochemistry, 2000)
These volumes are of interest to bioscientists and to historians alike. Many authors, both as individuals and as scientists, lived and worked in the 'age of extremes' in the so-called 'short 20th century', and yet contributed significantly to the unprecedented development of life sciences in this period. These 'oral histories', set against a backdrop of the Second World War, Holocaust, and Stalinist terror, are thus of interest and relevance to older and younger generations alike. Perhaps the lessons learned from these first-hand accounts may contribute in some way to ensuring that future scientists can enjoy the fascination of science undisturbed by the avoidable tragedy of man-made events. The contributors to this volume in the Comprehensive Biochemistry series encompass a wide variety of experiences in many different countries and in very different fields of biochemistry. Some have worked close to the laboratory bench throughout their scientific life and are continuing to do so. Others have been closely engaged in organizational matters, both nationally and internationally. All mention incidents in their own career or have observed those in others that will be of interest to future historians who will record and assess the period in which our contributors have lived and worked. It was an extremely exciting time for the life sciences. It was also a period of major and often tragic historical events that deeply affected the life and work of the generation to which our contributors belong.